Uprooting the Mosalaki: Changing institutions and livelihood impacts at Kelimutu National Park - Batiran, Karno; Fisher, Micah R.; Verheijen, Bart; Sirimorok, Nurhady; Sahide, Muhammad Alif K. (Forest and Society, 2023)
Studies on interactions between national parks and Indigenous Peoples in Indonesia have gained much attention in recent years, which mainly examine eviction, boundary disputes, and remediation. This research focuses on changing institutions since the establishment of Kelimutu National Park, foregrounding socio-cultural and livelihood impacts over time. This study involves in-depth interviews, FGDs, and observations from April to May 2019 and revisiting in November 2021. Findings highlight changing traditional institutions (Mosalaki) uprooted by the formal National Park governing authority. Such transitions also shift governing authority over natural resources access and control in ways that negatively affect the livelihoods of the Lio people of Kelimutu.